Detachable ultrathin rechargeable battery structure and processing method thereof
Through laser micro-nano processing and microfluidic control technology, the three-dimensional conductive network and self-healing packaging layer are constructed, and combined with magnetic connection, the ultra-thin battery is efficiently powered and repetitively disassembled on the curved surface, solving the problems of micro-powered technology in curved surface fitting and disassembly maintenance.
Patent Information
- Application Number
- CN202510623638.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-08-01
AI Technical Summary
The existing micro-powered technology is difficult to compatible with ultra-thin form, curved conformal fit and removable maintenance, resulting in contact gaps between batteries and equipment and mechanical damage, which cannot meet the long-term use needs of medical equipment.
Laser micro-nano processing is used to build a three-dimensional conductive network, combine microfluidic directional deposition technology to form a curved surface adaptive electrode array, and achieve accurate conformal bonding and repeatable disassembly between the battery and the biological curved surface through self-healing ion gel packaging and magnetic electrical connection layer.
It realizes the high energy density power supply of ultra-thin flexible batteries on the curved surface, and has the functions of curved conformal bonding and repeated lossless disassembly, solving the failure and disassembly damage problems of traditional batteries in mechanical bonding and curved surface bonding.
Smart Images

Figure CN120413828A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular, to a detachable ultra-thin rechargeable battery structure and a processing method thereof. Background Art
[0002] With the rapid development of micro medical devices such as smart contact lenses and subcutaneous implant monitors, their power supply systems face strict requirements: the battery needs to provide continuous milliwatt-level power output within a thickness of ≤0.5 mm, and at the same time adapt to the curved surface of the eyeball (curvature radius 7-8 mm) or the irregular surface of biological tissues. Industry data shows that 23% of existing products are forced to be externally placed due to the too large volume of the power supply module, and 41% of the devices have a service life of less than 3 years due to non-replaceable batteries. This exposes the core contradiction that the current micro power supply technology is difficult to be compatible with ultra-thin form, conformal fitting on the curved surface and detachable maintenance.
[0003] The current mainstream solutions adopt solid-state thin-film batteries (such as LiPON system) or flexible lithium batteries. Taking flexible batteries as an example, their thickness of 0.8 mm is achieved by thermally pressing and encapsulating a polyimide substrate and a lithium foil electrode, but there are two key defects: (1) Irreversible structural damage: The battery and the device are fixed by epoxy resin bonding. During disassembly, the electrode layer is peeled off due to mechanical stress (showing a capacity attenuation after 5 disassembly times); (2) Lack of curved surface adaptation: When a flat-structured battery is implanted into a curved surface device, there is a contact gap of ≥15%, resulting in local overheating.
[0004] These defects directly lead to the inability of the existing technology to meet the dual requirements of medical devices for regularly replacing batteries and precisely fitting biological curved surfaces. Summary of the Invention
[0005] The purpose of the present invention is to provide a detachable ultra-thin rechargeable battery structure and a processing method thereof to solve the above technical problems.
[0006] To achieve this purpose, the present invention adopts the following technical solutions: A processing method of a detachable ultra-thin rechargeable battery structure includes the following steps: Construct a three-dimensional conductive network on the surface of a boron nitride / graphene composite film through laser micro-nano processing to form a flexible substrate with a grid-shaped conduction path; Adopt a microfluidic directional deposition device to alternately deposit a positive electrode quantum dot layer and a negative electrode quantum dot layer on the surface of the flexible substrate to form an electrode array with curved surface adaptability; Inject a self-healing ionic gel on the surface of the electrode array and form a gradient cross-linked electrolyte encapsulation layer through a photocuring process; Integrate shape memory alloy contacts and a micro magnetic array on the outer surface of the electrolyte encapsulation layer, and form a magnetically attachable electrical connection layer that can be repeatedly disassembled through magnetron sputtering; Place the multi-layer structure in a biocompatible encapsulation film, and perform vacuum hot pressing using a curvature matching mold to obtain a battery body that conformally adheres to the target curved surface.
[0007] Optionally, construct a three-dimensional conductive network on the surface of the boron nitride / graphene composite film through laser micro-nano processing to form a flexible substrate with a grid-shaped conduction path, specifically including the following steps: Disperse boron nitride nanosheets and graphene oxide in deionized water at a mass ratio of 3:7. After forming a film by vacuum filtration, perform annealing treatment at 1200 °C in an argon atmosphere to obtain a boron nitride / graphene composite film substrate with a target thickness and surface roughness; Use a laser component to pre-scan the surface of the composite film substrate, and based on the reflection spectrum, dynamically adjust the laser power and scanning speed in real time to make the curvature deviation between the focal plane and the film surface tend to a preset interval for dynamic calibration of the laser parameters; Continue to use the laser component to perform layer-by-layer processing along the thickness direction of the composite film substrate. The first layer etches a polygon grid with a first depth at a first spacing, and the second layer etches a three-dimensional branch channel with a second depth at a preset offset and inclination angle at the bottom of the polygon grid to form a three-dimensional conductive network that penetrates the film surface and the interior; Fill silver nanowires into the etched three-dimensional conductive network, drive the silver nanowires to be directionally arranged along the three-dimensional branch channels through a pulsed electric field, and then perform in-situ sintering at 400 °C to form a continuous conductive path; Perform laser micro-melting treatment on the surface of the continuous conductive network to form a fillet transition with a preset radius at the edges of the polygon grid, and obtain a flexible substrate with qualified surface resistance and anti-bending times.
[0008] Optionally, use a microfluidic directed deposition device to alternately deposit a positive electrode quantum dot layer and a negative electrode quantum dot layer on the surface of the flexible substrate to form an electrode array with curvature adaptability, specifically including the following steps: Disperse indium phosphide quantum dots and molybdenum sulfide quantum dots in ionic liquids respectively. Add 0.5 wt% polyaniline conductive agent to the positive electrode liquid and 0.3 wt% carbon nanotube dispersant to the negative electrode liquid, and perform ultrasonic treatment to obtain a stable suspension with an absolute value of the target Zeta potential to prepare a quantum dot dispersion; Construct a microfluidic chip with curvature adaptability, and the microfluidic chip has a microfluidic channel design; Apply a preset alternating electric field between the flexible substrate and the microfluidic chip. During the positive electrode deposition stage, turn on the positive electric field to drive the indium phosphide quantum dots to be directionally enriched along the nodes of the three-dimensional conductive grid to form a positive electrode layer, and control the single-layer deposition thickness within a first thickness range; After the deposition of the positive electrode layer is completed, argon plasma is introduced for interlayer interface treatment, and then micro-pits are formed on the surface of the deposited layer. After that, it is switched to a molybdenum disulfide quantum dot suspension for reverse electric field deposition to form the negative electrode layer.
[0009] Optionally, after the single-layer deposition is completed, argon plasma is introduced to form micro-pits on the surface of the deposited layer, and then it is switched to a molybdenum disulfide quantum dot suspension for reverse electric field deposition to perform interlayer interface treatment. After that, it further includes: Adjust the deposition parameters through in-situ impedance monitoring. When the thickness of the electrode layer reaches the target value, linearly reduce the electric field strength to a preset strength, and at the same time increase the flow rate of the microfluidic channel from the first flow rate to the second flow rate to achieve a gradient distribution of the porosity at the top of the electrode layer; After the deposition is completed, apply a temperature-pressure coupling field to make the electrode layer plastically deform along the curvature of the flexible substrate, and finally obtain a curved electrode array with qualified curvature adaptation deviation and surface resistance difference.
[0010] Optionally, the bottom of the microfluidic chip fits the curvature of the flexible substrate, and a microfluidic channel with a gradient change in width is arranged on the top. The inner wall of the microfluidic channel is modified with carboxyl functional groups to enhance the adsorption of quantum dots; The microfluidic channel transitions from a first width gradient at its inlet to a second width at its outlet, where the first width is greater than the second width.
[0011] Optionally, self-healing ionic gel is injected onto the surface of the electrode array, and a gradient cross-linked electrolyte encapsulation layer is formed through a photocuring process, which specifically includes the following steps: Prepare a composite gel precursor; Inject the composite gel precursor solution onto the surface of the electrode array using an array of micro-needles, and cooperate with vacuum negative pressure to make the gel penetrate to a preset depth rate of the pores of the electrode layer. Synchronously apply pulsed air pressure to eliminate bubble defects for micro-region gradient injection; Under the synergistic action of an ultraviolet light source and a dynamic photomask, control the exposure intensity to gradually decrease from a first light intensity in the central region to a second light intensity in the edge region to form an encapsulation layer with a continuously changing cross-linking density gradient. During the curing process, maintain the matrix within a preset temperature range; Anneal the cured encapsulation layer in a nitrogen environment at 60 °C for 2 hours, repair the micro-cracks through a dynamic disulfide bond exchange reaction, and at the same time laser-etch stress release grooves with a third depth on the surface to finally obtain an electrolyte encapsulation layer with qualified elongation at break and ionic conductivity.
[0012] Optionally, the specific process of the composite gel precursor is as follows: Mix an ionic liquid containing a disulfide bond, an acrylate monomer, and a photoinitiator in a volume ratio of 75:22:3, and simultaneously inject titanium nitride nanowires as a conductive reinforcing phase, and ultrasonically oscillate at 40 °C to form a composite gel precursor with controllable viscosity.
[0013] Optionally, a shape memory alloy contact and a micro magnetic array are integrated on the outer surface of the electrolyte encapsulation layer, and a magnetically detachable electrical connection layer is formed by magnetron sputtering, specifically including: Perform plasma cleaning on the outer surface of the electrolyte encapsulation layer, and simultaneously laser etch to form micro-grooves with a fourth depth and distributed in an array. The inner walls of the micro-grooves are modified with an amino silane coupling agent; Deposit a shape memory alloy thin film in the micro-grooves, and etch the shape memory alloy thin film by focused ion beam to form contact units with a first diameter; Adopt a mask plate positioning method to sputter a composite layer of NdFeB magnetic powder and iron cobalt alloy in the gap region between the contact units, and apply a 0.5T gradient magnetic field during the magnetic field orientation process to form an anisotropic magnetic unit array; wherein, the field strength ratio of the gradient magnetic field in the X / Y / Z directions is 1:0.8:0.6.
[0014] Optionally, after adopting the mask plate positioning method to sputter a composite layer of NdFeB magnetic powder and iron cobalt alloy in the gap region between the contact units, applying a 0.5T gradient magnetic field during the magnetic field orientation process to form an anisotropic micro magnetic array, it further includes: Magnetron sputter a titanium / gold composite transition layer at the interface between the contact unit and the micro magnetic array, and then perform pulsed laser annealing in a vacuum environment to form a diffusion bonding interface; Apply a 0.3T test magnetic field to detect the magnetic suction force distribution, adjust the flatness of the contact unit through the shape memory effect, and obtain a magnetically detachable electrical connection layer with qualified contact resistance and magnetic adsorption force stability through laser trimming.
[0015] The present invention also provides a detachable ultra-thin rechargeable battery structure, adopting the processing method of the detachable ultra-thin rechargeable battery structure as described above. The detachable ultra-thin rechargeable battery structure specifically includes: A flexible substrate, on the surface of which a grid-shaped conductive path is etched; A positive electrode layer, in which indium phosphide quantum dots are directionally deposited along the conductive path to form a positive electrode array; A negative electrode layer, in which molybdenum sulfide quantum dots are alternately stacked with the positive electrode quantum dot layer, and the interlayer interface is treated by plasma; An electrolyte layer, an ionic gel encapsulation layer including a disulfide bond, and the crosslinking density changes continuously in a gradient; A magnetron electrical connection layer, including a shape memory alloy contact and a micro magnetic array, and a diffusion bonding interface.
[0016] Compared with the prior art, the present invention has the following beneficial effects: Firstly, a three-dimensional grid-shaped conductive path is etched on the surface of the boron nitride / graphene composite film by laser micro-nano processing to construct a flexible substrate; then, positive and negative quantum dot layers are alternately stacked on the substrate by microfluidic directed deposition technology to form a curved surface adaptive electrode array; then, a self-healing ionic gel is injected into the electrode array and a gradient cross-linked electrolyte encapsulation layer is formed by photocuring; further, a shape memory alloy contact and a micro magnetic array are integrated on the outer surface of the encapsulation layer to construct a magnetically attracted detachable electrical connection layer; the multi-layer structure is wrapped in a biocompatible encapsulation film and vacuum hot-pressed by a curvature matching mold to realize a battery body that is precisely conformal to the target curved surface; this process improves the conductivity of the substrate through a three-dimensional honeycomb conductive network while maintaining an ultra-thin thickness, the deposition of quantum dot electrodes increases the energy density, the gradient cross-linked electrolyte encapsulation layer combines self-healing properties, and the magnetically controlled interface design supports lossless disassembly. The ultra-thin flexible battery meets the high energy density power supply requirements while taking into account the functions of curved surface conformal fitting and repeated lossless disassembly. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.
[0018] The structures, ratios, sizes, etc. shown in the drawings of this specification are only used to cooperate with the content disclosed in the specification for those who are familiar with this technology to understand and read, and are not used to limit the limited conditions under which the present invention can be implemented. Therefore, they do not have technical substantive significance. Any modification of the structure, change of the proportional relationship, or adjustment of the size, without affecting the effects that the present invention can produce and the purposes that can be achieved, should still fall within the scope that the technical content disclosed by the present invention can cover.
[0019] Figure 1 It is one of the flow diagrams of the processing method of the detachable ultra-thin rechargeable battery structure in Embodiment 1; Figure 2 It is the second flow diagram of the processing method of the detachable ultra-thin rechargeable battery structure in Embodiment 1; Figure 3 It is the third flow diagram of the processing method of the detachable ultra-thin rechargeable battery structure in Embodiment 1; Figure 4 It is a schematic diagram of the detachable ultra-thin rechargeable battery structure in Embodiment 2; Figure 5 It is a hierarchical structure diagram of the detachable ultra-thin rechargeable battery structure in Embodiment 2. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0020] In order to make the objectives, features, and advantages of the present invention more obvious and understandable, the following will clearly and completely describe the technical solutions in the embodiments of the present invention with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the embodiments described below are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0021] In the description of the present invention, it should be understood that the orientation or positional relationship indicated by the terms "upper", "lower", "top", "bottom", "inner", "outer", etc. is based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be construed as a limitation to the present invention. It should be noted that when a component is considered to be "connected" to another component, it can be directly connected to the other component or there may be an intermediate component present at the same time.
[0022] The following further illustrates the technical solutions of the present invention with reference to the accompanying drawings and through specific embodiments.
[0023] Embodiment 1: Combined with Figures 1 to 3 As shown, the embodiment of the present invention provides a processing method for a detachable ultra-thin rechargeable battery structure, including the following steps: S1. Construct a three-dimensional conductive network on the surface of the boron nitride / graphene composite film through laser micro-nano processing to form a flexible substrate with a grid-like conductive path; Using the boron nitride / graphene composite film as the substrate, the three-dimensional grid-like conductive path is etched by laser micro-nano processing technology. The high insulation of boron nitride and the high conductivity of graphene are complementary. Laser processing realizes the formation of micron-scale structures by controlling the energy density. The three-dimensional grid design establishes a three-dimensional conductive channel while maintaining the flexibility of the substrate, significantly improving the charge transfer efficiency. Compared with the traditional two-dimensional conductive layer, this structure makes the current distribution more uniform and effectively reduces the interface resistance.
[0024] S2. Use a microfluidic directed deposition device to alternately deposit a positive quantum dot layer and a negative quantum dot layer on the surface of the flexible substrate to form an electrode array with curvature adaptability; The alternating stacking of the positive and negative quantum dot layers is achieved through a microfluidic directed deposition device. The microfluidic technology utilizes the principle of hydrodynamics to control the flow pattern of the quantum dot suspension and adjusts the deposition angle in conjunction with the change in the substrate curvature. The alternating deposition process enables the positive and negative electrode materials to form an interlaced structure at the microscale, increasing the effective reaction area. The curved surface adaptability design avoids the cracking of the electrode layer in the bent state through a stress release mechanism, enhancing the integrity of the electrode structure.
[0025] S3. Inject a self-healing ionic gel onto the surface of the electrode array and form a gradient cross-linked electrolyte encapsulation layer through a photocuring process. The injection of the self-healing ionic gel utilizes the reversible cleavage-recombination characteristics of dynamic disulfide bonds, endowing the electrolyte layer with the ability to autonomously repair microcracks. The gradient photocuring process forms a continuous cross-linked structure from dense to loose in the encapsulation layer by regulating the ultraviolet light intensity distribution. This gradient design takes into account both the interfacial bonding strength (dense region) and the ion transport efficiency (loose region), achieving a balance between mechanical stability and electrochemical performance.
[0026] S4. Integrate shape memory alloy contacts and a micro magnetic array on the outer surface of the electrolyte encapsulation layer and form a detachable magnetic electrical connection layer through magnetron sputtering. The shape memory alloy contacts are based on the thermoelastic martensitic phase transformation characteristics of NiTiNOL alloy and automatically recover the preset shape at body temperature, ensuring the reliability of electrical contact. The micro magnetic array adopts an NdFeB / cobalt iron composite structure, and the magnetic domains are directionally arranged through magnetron sputtering to generate a stable gradient magnetic field. The magnetic connection realizes physical connection through non-contact adsorption force and forms a dual protection mechanism in combination with the shape memory effect, significantly reducing the mechanical wear caused by repeated disassembly.
[0027] S5. Place the multi-layer structure in a biocompatible encapsulation film and perform vacuum hot pressing using a curvature-matching mold to obtain a battery body that conformally adheres to the target curved surface.
[0028] The low elastic modulus (≈1MPa) and high oxygen permeability of the biocompatible PDMS encapsulation film meet the requirements of biocompatibility with biological tissues. The curvature-matching mold uses reverse engineering to obtain the three-dimensional data of the target curved surface, and the vacuum hot pressing process causes the encapsulation film to undergo plastic deformation by precisely controlling the temperature-pressure curve. The conformal adhesion structure eliminates the interfacial stress concentration, avoids the peeling of the encapsulation layer caused by mechanical mismatch, and at the same time ensures the seamless integration of the battery with biological tissues.
[0029] The working principle of the present invention is as follows: First, a three-dimensional grid-shaped conductive path is etched on the surface of the boron nitride / graphene composite film by laser micro-nano processing to construct a flexible substrate; then, positive and negative quantum dot layers are alternately stacked on the substrate by microfluidic directed deposition technology to form a curved surface adaptive electrode array; then, a self-healing ionic gel is injected into the electrode array and a gradient cross-linked electrolyte encapsulation layer is formed by photocuring; further, a shape memory alloy contact and a micro magnetic array are integrated on the outer surface of the encapsulation layer to construct a magnetically attracted detachable electrical connection layer; the multi-layer structure is wrapped in a biocompatible encapsulation film and vacuum hot-pressed by a curvature matching mold to realize a battery body that is precisely conformally attached to the target curved surface; this process improves the conductivity of the substrate through a three-dimensional honeycomb conductive network while maintaining an ultra-thin thickness, the deposition of quantum dot electrodes increases the energy density, the gradient cross-linked electrolyte encapsulation layer combines self-healing characteristics, and the magnetically controlled interface design supports lossless disassembly. The ultra-thin flexible battery meets the high-energy density power supply requirements while taking into account the functions of curved surface conformal attachment and repeated lossless disassembly.
[0030] In this embodiment, specifically, step S1 specifically includes the following steps: S11, dispersing boron nitride nanosheets and graphene oxide in deionized water at a mass ratio of 3:7, forming a film by vacuum filtration, and then annealing at 1200 °C in an argon atmosphere to obtain a boron nitride / graphene composite film substrate with a target thickness and surface roughness; In this step, by controlling the mass ratio of boron nitride nanosheets to graphene oxide to be 3:7, high-temperature annealing treatment is carried out after forming a film by vacuum filtration. The combination of the insulation of boron nitride and the conductivity of graphene can balance the dielectric properties and conductive basis of the composite film. Annealing in argon at 1200 °C can effectively reduce the oxygen-containing groups in graphene oxide, improve the conductivity, and at the same time avoid material oxidation. The vacuum filtration process can ensure the compactness of the stacking between nanosheets and provide a uniform substrate surface for subsequent laser processing.
[0031] S12, pre-scanning the surface of the composite film substrate with a laser component, and dynamically calibrating the laser parameters based on the reflection spectrum in real time to make the curvature deviation between the focal plane and the film surface tend to a preset interval; By combining laser pre-scanning with real-time feedback of the reflection spectrum to dynamically calibrate the laser parameters, the processing accuracy problem caused by the curvature deviation of the composite film surface is solved. The reflection spectrum can sensitively capture the changes in the surface morphology of the material. By adjusting the laser power and scanning speed, the focal plane can be dynamically matched to the actual curvature of the film. This process avoids the problems of uneven etching depth or local ablation defects caused by the unevenness of the substrate in traditional laser processing, and ensures the uniformity of the subsequent three-dimensional network structure. The dynamic calibration mechanism significantly improves the controllability and repeatability of laser micro-nano processing.
[0032] S13. Continue to perform layer-by-layer processing on the composite film substrate along the thickness direction using a laser assembly. In the first layer, a polygonal grid with a first depth is etched at a first spacing. In the second layer, three-dimensional branched channels with a second depth are etched at the bottom of the polygonal grid with a preset offset and tilt angle, forming a three-dimensional conductive network that penetrates the film surface and interior. Preferably, in the first layer, hexagonal grooves with a spacing of 20 μm and a depth of 5 μm are etched. In the second layer, three-dimensional branched channels with a depth of 8 μm are etched at the bottom of the grooves with an offset of 10 μm and a tilt angle of 45°.
[0033] The layer-by-layer laser processing strategy constructs a three-dimensional network through two-stage etching: the first-layer polygonal grid forms the main surface conductive framework, and the second-layer three-dimensional branched channels extend into the interior with a preset offset and tilt angle. The polygonal grid design can disperse mechanical stress and improve the anti-bending ability of the substrate; the three-dimensional branched channels increase the internal conductive path density through the tilt angle design and avoid the defect of easy fracture of vertical channels. The coordinated control of the layer-by-layer parameters (spacing, depth, offset) realizes the penetration of the surface-internal conductive network, maximizing the conductive area and structural reliability within a limited thickness.
[0034] S14. Fill silver nanowires into the etched three-dimensional conductive network. Drive the silver nanowires to align along the three-dimensional branched channels through a pulsed electric field, and then in-situ sinter at 400 °C to form a continuous conductive path. The pulsed electric field drive aligns the silver nanowires along the axial direction of the three-dimensional branched channels, reducing the number of inter-wire lap joints and lowering the interface resistance. In-situ sintering at 400 °C promotes the formation of chemical bonding between the silver nanowires and the composite film substrate, enhancing the mechanical stability of the conductive network.
[0035] S15. Perform laser micro-melting treatment on the surface of the continuous conductive network to form a fillet transition with a preset radius at the edges of the polygonal grid, obtaining a flexible substrate with qualified surface resistance and anti-bending times.
[0036] The laser micro-melting treatment forms a fillet transition at the edges of the polygonal grid through local energy control. Its core advantage is to eliminate stress concentration at sharp corners. The fillet design with a preset radius can evenly disperse the shear stress during the bending process, significantly improving the anti-fatigue performance. The precise matching of the process parameters (energy density, action time) avoids the deformation of the conductive network caused by excessive melting, maintaining a low surface resistance while enabling the flexible substrate to meet the mechanical reliability requirements of repeated bending.
[0037] In this embodiment, specifically, step S2 specifically includes the following steps: S21. Disperse indium phosphide quantum dots and molybdenum sulfide quantum dots in ionic liquids respectively. Add 0.5 wt% polyaniline conductive agent to the positive electrode liquid and 0.3 wt% carbon nanotube dispersant to the negative electrode liquid, and perform ultrasonic treatment to obtain a stable suspension with the target absolute value of Zeta potential to prepare a quantum dot dispersion liquid; wherein, the Zeta potential is an index to measure the surface charge stability of particles in a solution, and the larger the absolute value, the more stable the dispersion liquid and the less likely to agglomerate.
[0038] By combining a conductive agent and a dispersant with specific ratios (0.5 wt% polyaniline added to the positive electrode and 0.3 wt% carbon nanotubes added to the negative electrode) to disperse quantum dots with ionic liquids, the stability control of the suspension is achieved. The selection of indium phosphide and molybdenum sulfide quantum dots takes into account the electrochemical activity matching of the positive and negative electrodes; polyaniline as a conductive agent can enhance the charge transfer efficiency of the positive electrode, while the carbon nanotube dispersant can inhibit the agglomeration of quantum dots at the negative electrode. Ultrasonic treatment combined with Zeta potential regulation ensures uniform surface charge distribution of quantum dots and avoids local aggregation defects caused by electrostatic repulsion or attraction during the deposition process. The high thermal stability and low volatility of ionic liquids as a dispersion medium provide a stable solution environment for subsequent microfluidic deposition.
[0039] S22. Construct a microfluidic chip with surface adaptability, and the microfluidic chip has a microfluidic channel design; The core of the design of the surface-adaptive microfluidic chip lies in the dynamic matching of the geometric parameters of the microfluidic channel with the curvature of the target surface. The microfluidic channel is constructed by a flexible material (such as PDMS), and its deformation ability can fit the curvature change of the substrate to ensure the uniform flow of the quantum dot suspension on the curved substrate.
[0040] S23. Apply a preset alternating electric field between the flexible substrate and the microfluidic chip. During the positive electrode deposition stage, turn on the positive electric field to drive the indium phosphide quantum dots to be directionally enriched along the nodes of the three-dimensional conductive grid to form a positive electrode layer, and control the single-layer deposition thickness within the first thickness range; The preset alternating electric field drives the directional enrichment of quantum dots, and its mechanism is based on the spatial manipulation of charged quantum dots by the electric field force. The positive electric field enables the positively charged indium phosphide quantum dots to be preferentially adsorbed on the nodes of the three-dimensional conductive grid (high electric field intensity region) to form a continuous and high-density positive electrode layer. The control of the single-layer thickness (such as nanoscale precision) is achieved through the coordinated adjustment of the electric field intensity and the deposition time, avoiding stress concentration caused by excessive thickness or insufficient capacity caused by too thin. The selective deposition of the three-dimensional grid nodes enhances the mechanical interlocking effect between the electrode layer and the substrate and improves the interface bonding strength.
[0041] S24. After completing the deposition of the positive electrode layer, introduce argon plasma for interlayer interface treatment, then form micro-pits on the surface of the deposition layer, and then switch to the molybdenum sulfide quantum dot suspension for reverse electric field deposition to form a negative electrode layer.
[0042] Argon plasma treatment removes interlayer impurities and activates the surface through high-energy particle bombardment, while forming micron-scale pits on the surface of the deposited layer. The increased roughness of the pits can enhance the physical anchoring effect between the subsequent negative electrode layer and the positive electrode layer, reducing the interlayer contact resistance. After switching to the reverse electric field, negatively charged molybdenum disulfide quantum dots preferentially fill the pit regions and form an interdigitated structure with the positive electrode layer, effectively suppressing the risk of interlayer delamination during charge and discharge processes. The timing control of plasma treatment and electric field switching ensures the interfacial compatibility and structural stability of the positive and negative electrode layers.
[0043] S25. Adjust the deposition parameters by in-situ impedance monitoring. When the thickness of the electrode layer reaches the target value, linearly reduce the electric field strength to the preset strength, and at the same time increase the flow rate of the microfluidic channel from the first flow rate to the second flow rate to achieve a gradient distribution of porosity at the top of the electrode layer (15% at the bottom → 35% at the top); the thickness of the electrode layer refers to the sum of the thicknesses of the positive electrode layer and the negative electrode layer.
[0044] In-situ impedance monitoring dynamically adjusts the electric field strength and flow rate parameters by real-time feedback of the electrode layer thickness and interfacial state (such as porosity, contact resistance). The linearly decreasing electric field strength can slow down the deposition rate of quantum dots and avoid excessive densification at the top; the increased flow rate forms a gradient pore structure (dense at the bottom, loose at the top) at the top of the electrode layer through the fluid flushing effect. The gradient pore design takes into account both the ion transport efficiency (high-porosity region) and the electron conduction ability (dense region), while alleviating the volume expansion stress during charge and discharge processes and improving the cycle stability.
[0045] S26. Apply a temperature-pressure coupling field after deposition to cause the electrode layer to undergo plastic deformation along the curvature of the flexible substrate, and finally obtain a curved electrode array with qualified curvature adaptation deviation and surface resistance difference.
[0046] The temperature-pressure coupling field realizes the curvature adaptation of the electrode layer through thermoplastic deformation. When the temperature rises above the glass transition point of the material, the electrode layer undergoes plastic flow under the action of pressure and conforms to the curvature of the flexible substrate; the deformed state is retained after cooling and setting. The precise matching of the process parameters (temperature range, pressure value, action time) avoids electrode cracking or conductive network fracture caused by excessive deformation, and at the same time ensures the electrical performance consistency after deformation through surface resistance difference monitoring, finally achieving the balance between curved conformal fitting and electrical performance.
[0047] In this embodiment, further description is as follows. The bottom of the microfluidic chip conforms to the curvature of the flexible substrate, and a microfluidic channel with a gradient change in width is set at the top. The inner wall of the microfluidic channel is modified with carboxyl functional groups to enhance the adsorption of quantum dots; the microfluidic channel transitions from the first width gradient at its inlet to the second width at the outlet, where the first width is greater than the second width. Optionally, the inlet is 50μm → the outlet is 20μm.
[0048] In this embodiment, specifically, step S3 specifically includes the following steps: S31. Prepare a composite gel precursor; the specific process is as follows: Mix an ionic liquid containing a disulfide bond, an acrylate monomer, and a photoinitiator in a volume ratio of 75:22:3, and simultaneously inject titanium nitride nanowires as a conductive reinforcing phase, and ultrasonically oscillate at 40 °C to form a composite gel precursor with controllable viscosity.
[0049] By mixing an ionic liquid containing a disulfide bond, an acrylate monomer, and a photoinitiator in a volume ratio of 75:22:3, the balance of self-healing ability (dynamic exchange of disulfide bonds), mechanical strength (polymerization of acrylate), and photocuring efficiency is synergistically achieved. The introduction of titanium nitride nanowires as a conductive reinforcing phase can make up for the insufficient conductivity of the ionic liquid, and its high aspect ratio characteristics form a three-dimensional conductive path under ultrasonic dispersion (40 °C).
[0050] S32. Use an array of microneedles to inject the composite gel precursor liquid onto the surface of the electrode array, cooperate with vacuum negative pressure to make the gel penetrate to a preset depth rate in the pores of the electrode layer, and simultaneously apply pulsed air pressure to eliminate bubble defects for micro-region gradient injection; The injection of the array of microneedles combined with vacuum negative pressure and pulsed air pressure solves the problem of pore filling in the ultra-thin electrode layer: Vacuum negative pressure drives the gel to penetrate to the preset depth rate (such as 80% of the electrode pores), avoiding the coverage of electrode active substances caused by excessive penetration; Pulsed air pressure destroys the bubble nucleation conditions through periodic pressure fluctuations, eliminating micron-sized bubble defects. The spacing of the microneedle array matches the electrode structure, realizing local precise injection, preventing the gel from overflowing and contaminating non-target areas, and ensuring the clarity of the encapsulation layer interface and the integrity of the electrode function.
[0051] S33. Under the synergistic action of an ultraviolet light source and a dynamic photomask, control the exposure intensity to decrease gradually from the first light intensity in the central area to the second light intensity in the edge area, forming an encapsulation layer with a continuously varying crosslinking density gradient, and maintaining the matrix within a preset temperature range during the curing process; The gradual decrease of the ultraviolet light intensity (high in the central area → low in the edge area) is regulated by the dynamic photomask, making the crosslinking density of the encapsulation layer change continuously in a gradient. The high crosslinking density in the central area provides mechanical support, and the low crosslinking density in the edge area improves flexibility to adapt to curved surface deformation, overall reducing the interfacial stress between the encapsulation layer and the electrode layer. The curing temperature control (such as 25 ± 2 °C) suppresses the difference in thermal-induced volume expansion, avoiding microcracks caused by curing shrinkage. This gradient design takes into account the rigid-flexible transition requirements of the encapsulation layer, improving the structural durability during the battery cycling process.
[0052] S34, Two-stage self-healing treatment: Anneal the cured encapsulation layer in a nitrogen environment at 60 °C for 2 hours to repair microcracks through dynamic disulfide bond exchange reaction. At the same time, laser etch stress relief grooves with a third depth of 5 - 8 μm on the surface to finally obtain an electrolyte encapsulation layer with qualified elongation at break and ionic conductivity.
[0053] Annealing at 60 °C in nitrogen activates the dynamic disulfide bond exchange reaction to repair microcracks inside the encapsulation layer and restore the ion transport path; Laser etching stress relief grooves with a depth of 5 - 8 μm guides the dispersion of external stress through the preset groove geometry distribution to inhibit crack propagation. The annealing temperature needs to be higher than the disulfide bond recombination threshold but lower than the glass transition temperature of the encapsulation layer to ensure the effectiveness of repair and prevent structural collapse. The two-stage treatment synergistically improves the self-healing ability and anti-fatigue performance of the encapsulation layer, ultimately meeting the ionic conductivity and anti-fracture indicators.
[0054] In this embodiment, specifically, step S4 specifically includes the following steps: S41, Perform plasma cleaning on the outer surface of the electrolyte encapsulation layer, and simultaneously laser etch micro-grooves with a fourth depth in an array distribution. The inner walls of the micro-grooves are modified with an amino-silane coupling agent; Plasma cleaning removes surface contaminants of the encapsulation layer by bombarding with high-energy particles and activates chemical groups. The simultaneously laser-etched array of micro-grooves (such as a 50 μm pitch) increases the effective contact area. After the inner walls are modified with an amino-silane coupling agent, its amino functional groups can form strong chemical bonds with the subsequently deposited shape memory alloy film, enhancing the interfacial bonding strength. Precise control of the groove depth (fourth depth) ensures that the contact units are flush with the surface of the encapsulation layer after being embedded, avoiding local stress concentration caused by protrusions and providing a flat substrate for the construction of the magnetic layer.
[0055] S42, Deposit a shape memory alloy film in the micro-grooves, and use a focused ion beam to etch the shape memory alloy film to form contact units with a first diameter; After depositing a shape memory alloy film (such as NiTi alloy), a focused ion beam (FIB) is used to etch contact units with a first diameter (such as 10 μm). The high-precision processing ability (nanoscale resolution) of FIB ensures the uniformity of contact sizes, and there is no thermal damage at the etched edges; The phase change characteristics of the shape memory alloy enable the contact units to recover the preset shape when the temperature or stress changes, ensuring the contact reliability after multiple disassembly. The array distribution design of the contact units matches the subsequent magnetic unit arrangement to optimize the current transmission path density.
[0056] S43, Adopt a mask plate positioning method to sputter a composite layer of NdFeB magnetic powder and iron-cobalt alloy in the gap area between the contact units, and apply a 0.5 T gradient magnetic field during the magnetic field orientation process to form an anisotropic magnetic unit array; Among them, the field strength ratio of the gradient magnetic field in the X / Y / Z directions is 1:0.8:0.6.
[0057] When sputtering the composite layer of NdFeB magnetic powder and iron-cobalt alloy on the mask plate, a gradient magnetic field with an X / Y / Z direction field strength ratio of 1:0.8:0.6 is applied to induce the magnetic powder to orient and arrange along the preset direction. This ratio design breaks the random distribution of magnetic domains through the gradient field strength difference, forming an anisotropic magnetic unit array (such as the direction perpendicular to the magnetization direction), improving the magnetic adsorption force per unit area; the addition of iron-cobalt alloy enhances the demagnetization resistance of the magnetic units, ensuring the stability of the magnetic attraction force after long-term use. The precise alignment of the mask plate avoids physical interference between the magnetic layer and the contact units.
[0058] S44, magnetron sputter a titanium / gold composite transition layer at the interface between the contact unit and the micro-magnetic array, and then perform pulsed laser annealing in a vacuum environment to form a diffusion bonding interface; The magnetron sputtering of the titanium / gold composite transition layer optimizes the interface performance through the laminated structure of the titanium layer (high bonding strength) and the gold layer (low contact resistance). Pulsed laser annealing (such as an energy density of 5 J / cm²) promotes atomic diffusion between the titanium / gold layer, the shape memory alloy, and the magnetic units, forming a metallurgical bonding interface, reducing the contact resistance and suppressing interface peeling. The vacuum environment avoids high-temperature oxidation and ensures the chemical stability of the transition layer. This combination of process parameters achieves a double improvement in electrical performance and mechanical reliability.
[0059] S45, apply a 0.3T test magnetic field to detect the magnetic attraction force distribution, adjust the flatness of the contact unit through the shape memory effect, and obtain a magnetically attracted electrical connection layer with qualified contact resistance and magnetic adsorption force stability through laser trimming.
[0060] Detect the magnetic attraction force distribution under a 0.3T test magnetic field, adjust the flatness of the contact unit by combining the shape memory effect (such as heating to the phase transition temperature) to eliminate local poor contact caused by processing errors; laser trimming (such as laser micro-ablative) selectively removes the overly high contacts to make the contact resistance distribution uniform. The stability of the magnetic attraction force is verified through multiple disassembly cycle tests to ensure that the attenuation rate of the adsorption force at the interface between the magnetic units and external devices is ≤5%. The parameter settings (such as the test magnetic field strength, trimming energy) are directly related to the achievement efficiency of the functional indicators.
[0061] Example 2: Combined with Figure 4 and Figure 5 As shown, the present invention also provides a detachable ultra-thin rechargeable battery structure, adopting the processing method of the detachable ultra-thin rechargeable battery structure in Example 1. The detachable ultra-thin rechargeable battery structure specifically includes: A flexible substrate 10 with a grid-shaped conductive path 11 etched on its surface.
[0062] A positive electrode layer 20, where indium phosphide quantum dots are directionally deposited along the conductive path to form a positive electrode array.
[0063] The negative electrode layer 30 is formed by alternately stacking molybdenum disulfide quantum dots and the positive electrode quantum dot layer, and the interfaces between layers are treated by plasma.
[0064] The electrolyte layer 40 includes an ionic gel encapsulation layer containing disulfide bonds, and the crosslinking density changes continuously in a gradient manner.
[0065] The magnetron electrical connection layer 50 includes a shape memory alloy contact and a micro magnetic array, as well as a diffusion bonding interface.
[0066] The beneficial effects of the present invention are as follows: Through the collaborative design of a flexible substrate conductive network, quantum dot gradient electrodes, a self-healing electrolyte layer, and a magnetic adsorption interface, it has the characteristics of ultra-thin flexibility, high energy density, and repeatable non-destructive disassembly: the grid conductive path improves the conductivity and anti-bending ability of the substrate; the alternate deposition of quantum dots combined with plasma interface treatment enhances the structural stability of the electrode and the ion transport efficiency; the gradient cross-linked electrolyte layer inhibits crack propagation and adapts to curved surface deformation through its self-healing function; the shape memory alloy contact and the anisotropic magnetic array achieve high-precision electrical connection and stable adsorption force, supporting the contact reliability to be maintained even after multiple disassembly. This structure effectively solves the problems of curved surface fitting failure, disassembly damage, and local overheating caused by mechanical bonding and rigid encapsulation in traditional flexible batteries, and is particularly suitable for implantable microelectronic devices that need to precisely fit biological surfaces and frequently replace batteries.
[0067] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements for some of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A processing method for a detachable ultra-thin rechargeable battery structure, characterized in that, It includes the following steps: Construct a three-dimensional conductive network on the surface of the boron nitride / graphene composite film by laser micro-nano processing to form a flexible substrate with a grid-like conductive path; Use a microfluidic directed deposition device to alternately deposit a positive electrode quantum dot layer and a negative electrode quantum dot layer on the surface of the flexible substrate to form an electrode array with surface adaptability; Inject a self-healing ionic gel on the surface of the electrode array and form a gradient cross-linked electrolyte encapsulation layer through a photocuring process; Integrate shape memory alloy contacts and a micro magnetic array on the outer surface of the electrolyte encapsulation layer and form a repeatedly detachable magnetic adsorption electrical connection layer through magnetron sputtering; Place the multi-layer structure in a biocompatible packaging film and perform vacuum hot pressing using a curvature matching mold to obtain a battery body that conformally fits the target curved surface.
2. The processing method of the detachable ultra-thin rechargeable battery structure according to claim 1, characterized in that, The step of constructing a three-dimensional conductive network on the surface of the boron nitride / graphene composite film by laser micro-nano processing to form a flexible substrate with a grid-like conductive path specifically includes the following steps: Disperse boron nitride nanosheets and graphene oxide in deionized water at a mass ratio of 3:
7. After forming a film by vacuum filtration, perform annealing treatment at 1200 °C in an argon atmosphere to obtain a boron nitride / graphene composite film substrate with a target thickness and surface roughness; Use a laser component to pre-scan the surface of the composite film substrate, and based on the reflection spectrum, adjust the laser power and scanning speed in real time to make the curvature deviation between the focal plane and the film surface tend to a preset interval for dynamic calibration of the laser parameters; Continue to use the laser component to perform layered processing along the thickness direction of the composite film substrate. The first layer etches a polygonal grid with a first depth at a first spacing, and the second layer etches a three-dimensional branch channel with a second depth at a preset offset and inclination angle at the bottom of the polygonal grid to form a three-dimensional conductive network that penetrates the film surface and the interior; Fill silver nanowires in the etched three-dimensional conductive network, drive the silver nanowires to be directionally arranged along the three-dimensional branch channels through a pulsed electric field, and then perform in-situ sintering at 400 °C to form a continuous conductive path; Perform laser micro-melting treatment on the surface of the continuous conductive network to form a fillet transition with a preset radius at the edge of the polygonal grid, and obtain a flexible substrate with qualified surface resistance and anti-bending times.
3. The processing method of the detachable ultra-thin rechargeable battery structure according to claim 1, characterized in that The step of using a microfluidic directed deposition device to alternately deposit a positive electrode quantum dot layer and a negative electrode quantum dot layer on the surface of the flexible substrate to form an electrode array with surface adaptability specifically includes the following steps: Disperse indium phosphide quantum dots and molybdenum sulfide quantum dots in ionic liquids respectively. Add 0.5 wt% polyaniline conductive agent to the positive electrode liquid and 0.3 wt% carbon nanotube dispersant to the negative electrode liquid, and perform ultrasonic treatment to obtain a stable suspension with an absolute value of the target Zeta potential to prepare a quantum dot dispersion liquid; Construct a microfluidic chip with surface adaptability, and the microfluidic chip has a microfluidic channel design; Apply a preset alternating electric field between the flexible substrate and the microfluidic chip. During the positive electrode deposition stage, turn on the positive electric field to drive the indium phosphide quantum dots to be directionally enriched along the three-dimensional conductive grid nodes to form a positive electrode layer, and the single-layer deposition thickness is controlled within a first thickness range; After the deposition of the positive electrode layer is completed, argon plasma is introduced for interlayer interface treatment, and then micro-pits are formed on the surface of the deposited layer. After that, it is switched to a molybdenum disulfide quantum dot suspension for reverse electric field deposition to form the negative electrode layer.
4. The processing method of the detachable ultra-thin rechargeable battery structure according to claim 3, characterized in that, After the completion of monolayer deposition, argon plasma is introduced to form micro-pits on the surface of the deposited layer. Then, it is switched to a molybdenum disulfide quantum dot suspension for reverse electric field deposition to perform interlayer interface treatment. After that, it further includes: Adjust the deposition parameters through in-situ impedance monitoring. When the thickness of the electrode layer reaches the target value, linearly reduce the electric field strength to a preset intensity, and at the same time increase the flow rate of the microfluidic channel from the first flow rate to the second flow rate to achieve a gradient distribution of porosity at the top of the electrode layer. After the deposition is completed, apply a temperature-pressure coupling field to make the electrode layer undergo plastic deformation along the curvature of the flexible substrate, and finally obtain a curved electrode array with qualified curvature adaptation deviation and surface resistance difference.
5. The processing method of the detachable ultra-thin rechargeable battery structure according to claim 4, characterized in that The bottom of the microfluidic chip conforms to the curvature of the flexible substrate, and a microfluidic channel with a gradient change in width is arranged at the top. The inner wall of the microfluidic channel is modified with carboxyl functional groups to enhance the adsorption of quantum dots. The microfluidic channel transitions from a first width gradient at its inlet to a second width at its outlet, where the first width is greater than the second width.
6. The processing method of the detachable ultra-thin rechargeable battery structure according to claim 1, characterized in that, Inject a self-healing ion gel on the surface of the electrode array, and form a gradient-crosslinked electrolyte encapsulation layer through a photocuring process, which specifically includes the following steps: Prepare a composite gel precursor. Inject the composite gel precursor solution onto the surface of the electrode array using an array of micro-needles, and cooperate with vacuum negative pressure to make the gel penetrate to a preset depth rate of the pores of the electrode layer. Synchronously apply pulsed air pressure to eliminate bubble defects for micro-region gradient injection. Under the synergistic action of an ultraviolet light source and a dynamic photomask, control the exposure intensity to decrease gradually from a first light intensity in the central region to a second light intensity in the edge region to form an encapsulation layer with a continuously varying gradient in crosslinking density. During the curing process, maintain the matrix within a preset temperature range. Anneal the cured encapsulation layer in a nitrogen environment at 60 °C for 2 hours, repair micro-cracks through dynamic disulfide bond exchange reactions, and at the same time laser etch stress relief grooves with a third depth on the surface to finally obtain an electrolyte encapsulation layer with qualified elongation at break and ionic conductivity.
7. The processing method of the detachable ultra-thin rechargeable battery structure according to claim 6, characterized in that, The specific process of the composite gel precursor is as follows: Mix an ionic liquid containing a disulfide bond, an acrylate monomer, and a photoinitiator in a volume ratio of 75:22:3, and simultaneously inject titanium nitride nanowires as a conductive reinforcement phase, and ultrasonically oscillate at 40 °C to form a composite gel precursor with controllable viscosity.
8. The processing method of the detachable ultra-thin rechargeable battery structure according to claim 1, characterized in that, Integrate shape memory alloy contacts and a micro magnetic array on the outer surface of the electrolyte encapsulation layer, and form a detachable magnetic electrical connection layer through magnetron sputtering, which specifically includes: Perform plasma cleaning on the outer surface of the electrolyte encapsulation layer, and simultaneously laser etch micro-grooves with a fourth depth distributed in an array. The inner walls of the micro-grooves are modified with an amino silane coupling agent. Deposit a shape memory alloy thin film in the micro-grooves, and etch the shape memory alloy thin film through a focused ion beam to form contact units with a first diameter. Adopt a mask plate positioning method, sputter a composite layer of NdFeB magnetic powder and iron-cobalt alloy in the gap area of the contact unit, apply a 0.5T gradient magnetic field during the magnetic field orientation process to form an anisotropic magnetic unit array; wherein, the field strength ratio of the gradient magnetic field in the X / Y / Z directions is 1:0.8:0.
6.
9. The processing method of the detachable ultra-thin rechargeable battery structure according to claim 8, characterized in that, The method of adopting a mask plate positioning method, sputtering a composite layer of NdFeB magnetic powder and iron-cobalt alloy in the gap area of the contact unit, applying a 0.5T gradient magnetic field during the magnetic field orientation process to form an anisotropic micro-magnetic array, further includes: Magnetron sputter a titanium / gold composite transition layer at the interface between the contact unit and the micro-magnetic array, and then perform pulsed laser annealing in a vacuum environment to form a diffusion bonding interface; Apply a 0.3T test magnetic field to detect the magnetic suction force distribution, adjust the flatness of the contact unit through the shape memory effect, and obtain a magnetically attracted electrical connection layer with qualified contact resistance and magnetic adsorption force stability through laser trimming.
10. A detachable ultra-thin rechargeable battery structure, characterized in that, Adopt the processing method of the detachable ultra-thin rechargeable battery structure as described in any one of claims 1 to 9, and the detachable ultra-thin rechargeable battery structure specifically includes: A flexible substrate, on the surface of which a grid-shaped conductive path is etched; A positive electrode layer, where indium phosphide quantum dots are directionally deposited along the conductive path to form a positive electrode array; A negative electrode layer, where molybdenum sulfide quantum dots are alternately stacked with the positive quantum dot layer, and the interface between layers is treated by plasma; An electrolyte layer, including an ionic gel encapsulation layer with disulfide bonds, and the crosslinking density changes continuously in a gradient; A magnetron electrical connection layer, including a shape memory alloy contact and a micro-magnetic array, as well as a diffusion bonding interface.
Citation Information
Patent Citations
Rechargeable ionic liquid dual-ion battery and preparation method therefor
CN107069022A
Cited By
Medium-free holographic optical element processing technology based on grinding and polishing parameters and medium-free holographic optical element
CN120742472A
Abrasive polishing parameter-based medium-free holographic optical element processing technology and medium-free holographic optical element
CN120742472B